Exploiting endocytosis for transfection of mRNA for cytoplasmatic delivery using cationic gold nanoparticles - Gustà, Muriel F.; Edel, Michael J.; Salazar, Vivian A.; Alvarez-Palomo, Belén; Juan, Manel; Broggini, Massimo; Damia, Giovanna; Bigini, Paolo; Corbelli, Alessandro; Fiordaliso, Fabio; Barbul, Alexander; Korenstein, Rafi; et al. (Frontiers in Immunology, 2023)
Gene therapy holds promise to cure various diseases at the fundamental level. For that, efficient carriers are needed for successful gene delivery. Synthetic ‘non-viral’ vectors, as cationic polymers, are quickly gaining popularity as efficient vectors for transmitting genes. However, they suffer from high toxicity associated with the permeation and poration of the cell membrane. This toxic aspect can be eliminated by nanoconjugation. Still, results suggest that optimising the oligonucleotide complexation, ultimately determined by the size and charge of the nanovector, is not the only barrier to efficient gene delivery. We herein develop a comprehensive nanovector catalogue comprising different sizes of Au NPs functionalized with two different cationic molecules and further loaded with mRNA for its delivery inside the cell. Tested nanovectors showed safe and sustained transfection efficiencies over 7 days, where 50 nm Au NPs displayed the highest transfection rates. Remarkably, protein expression was increased when nanovector transfection was performed combined with chloroquine. Cytotoxicity and risk assessment demonstrated that nanovectors are safe, ascribed to lesser cellular damage due to their internalization and delivery via endocytosis. Obtained results may pave the way to design advanced and efficient gene therapies for safely transferring oligonucleotides.